2018
DOI: 10.6118/jmm.2018.24.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Approaches to Atrophic Vaginitis in Postmenopausal Women: A Systematic Review with a Network Meta-analysis of Randomized Controlled Trials

Abstract: ObjectivesAtrophic vaginitis (AV), which is common in postmenopausal women, is characterized by vaginal dryness, dyspareunia, and discomfort. There are a variety of therapeutic agents for the treatment of AV, besides hormone replacement therapy. We performed this systematic review to compare the effectiveness of various therapies for symptom improvement in AV patients.MethodsWe searched the Cochrane Library, EMBASE, MEDLINE, and other literature (Google Scholar, Web of Science, and hand search) for studies pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…However, the majority of hot flushes usually waned after 4 weeks of ospemifene treatment 64 . The results are consistent with previous meta-analyses, which demonstrated superior efficacy and no major safety concerns with ospemifene compared with placebo, except for the prior NMA by Lee et al, 65 which failed to find statistically significant differences in outcomes 66-68 . However, the network used was different than that of the present study, as different comparators were included and, thus, different results are expected.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the majority of hot flushes usually waned after 4 weeks of ospemifene treatment 64 . The results are consistent with previous meta-analyses, which demonstrated superior efficacy and no major safety concerns with ospemifene compared with placebo, except for the prior NMA by Lee et al, 65 which failed to find statistically significant differences in outcomes 66-68 . However, the network used was different than that of the present study, as different comparators were included and, thus, different results are expected.…”
Section: Discussionsupporting
confidence: 88%
“…However, the network used was different than that of the present study, as different comparators were included and, thus, different results are expected. Nevertheless, results of the study by Lee et al 65 suggest that ospemifene was effective against dyspareunia, vaginal dryness, endometrial thickness, and percentage changes in superficial and parabasal cells. Real-world evidence also confirms the short- and long-term therapeutic value of ospemifene in routine clinical practice 69,70 .…”
Section: Discussionmentioning
confidence: 94%
“…Son varias las preparaciones de estrógenos locales que han demostrado disminuir los síntomas de la atrofia, incluyendo la sequedad vaginal, irritación, prurito, dispareunia y urgencia urinaria (2,3,13,14). Estos tratamientos también aumentan el flujo sanguíneo y la lubricación, lo que puede influir positivamente en la función sexual (2,15).…”
Section: Tabla No 2 Signos Clínicos Del Síndrome Genitourinario De La Menopausiaunclassified
“…In this systematic review, the results of a study of the five included studies showed that estrogen compared with HA improved the symptoms of vaginal atrophy with a statistically significant difference, 9 which is consistent with the systematic review results by Lee et al., who performed a meta-analysis on nine trials aimed at evaluating the effectiveness of several drugs in treatment atrophic vaginitis, and concluded that 30 mg/day of ospemifene (low-dose estrogen) from among other drugs had the most therapeutic effect on the improvement of surface cells and parabasal cells as well as the symptoms of dyspareunia and vaginal dryness, but this effect was not statistically significant. 16 Vaginal estrogen is a gold standard for the symptoms of atrophic vulvovaginitis. The side effects and systemic estrogen uptake are reduced significantly in topical use, but in some cases, it is often necessary to seek alternative methods.…”
Section: Discussionmentioning
confidence: 99%